The Influence of Pocket Money and Financial Literacy on STEBIS IGM Islamic Banking Students' Charity Interest - Fadilla Fadilla; Erdiansyah Erdiansyah (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2024)
The research seeks to examine the influence of pocket money and financial literacy on STEBIS IGM sharia banking students' interest in giving to charity. The population in this study was all 85 sharia banking students. The sampling technique in this research was incidental sampling, where the number of students who filled out the questionnaire was 64 people. Data analysis technique using multiple linear regression. The research results show that pocket money and financial literacy influence STEBIS IGM students' interest in giving to charity, both partially and simultaneously. Pocket money influences the interest in giving to charity of Stebis IGM sharia banking students. financial literacy influences the interest in giving to charity of Stebis IGM sharia banking students. The significance value of financial literacy is 0.003 with a t value of 3.05, meaning that if students increase their knowledge about alms, their interest in giving alms will also be high. Likewise with pocket money, the significance value is 0.008, which means that if pocket money increases, students will have an increased interest in giving alms.